2020
DOI: 10.5871/jba/008s2.133
|View full text |Cite
|
Sign up to set email alerts
|

The role of graduation programming in promoting early childhood development: an overview of the evidence

Abstract: It is widely understood that poverty undermines early childhood development (ECD). In turn, poor ECD reinforces intergenerational transmission of poverty. Comprehensive economic strengthening and social protection programmes, such as 'graduation programmes', may offer a 'double boon': they can improve ECD in the short term and break the intergenerational cycle of poverty in the long run. This article provides a comprehensive review of the state of the evidence regarding the role of graduation pogrammes in ECD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We reviewed the literature cited in each of the studies that met our criteria to identify additional studies. We also reviewed the studies cited in various review papers and reports (Evans and Popova, 2014;Sulaiman et al, 2016;Roelen et al, 2020;Bastagli et al, 2016;Hashemi and De Montesquiou, 2011;Sulaiman et al, 2016). We identified 30 studies that met our criteria.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the literature cited in each of the studies that met our criteria to identify additional studies. We also reviewed the studies cited in various review papers and reports (Evans and Popova, 2014;Sulaiman et al, 2016;Roelen et al, 2020;Bastagli et al, 2016;Hashemi and De Montesquiou, 2011;Sulaiman et al, 2016). We identified 30 studies that met our criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Only about half of the included studies provided any equity evidence (defined as subgroup or interaction effects), of which only 3 studies conducted sex-disaggregated analyses; findings demonstrated either no difference in intervention effects between boys and girls (2) or the intervention effects favoured boys only (1). Few studies specifically involved fathers, which may place increased caregiving burden on mothers, such as collecting food/cash transfers, attending intervention sessions, or complying with conditions of cash transfers; this has also been identified as an issue in graduation programmes for early child development [ 57 ]. More work is needed to investigate and ensure that these interventions benefit the most vulnerable children, thereby narrowing the health equity gap (SDG 10).…”
Section: Discussionmentioning
confidence: 99%
“…12 Only 15 studies report on child health outcomes and 20 studies on education outcomes. See also Roelen, Sherer, and Himmelstine (2020) for a review of impact on children. 13 See Bandiera et al 2017;Banerjee et al 2015;Bedoya et al 2019;Das et al 2016;de Mel, McKenzie, and Woodruff 2014;Holmes and Jones 2010;Kabeer et al 2012;Shoaf and Simanowitz 2019;Siddiki et al 2014;and World Bank 2020.…”
Section: Short-term Impactmentioning
confidence: 99%